EFFECT OF VARYING LEVELS OF NITROGEN AND SULPHUR ON GROWTH AND YIELD OF CORIANDER (CORIANDRUM SATIVUM L.) - C. B. PATEL; A. U. AMIN; A. L. PATEL (The Bioscan, 2013)
A field experiment was conducted on loamy sand soil of Agronomy Instructional Farm, Sardarkrushinagar Dantiwada Agricultural University, Sardarkrushinagar during rabi season of 2009-10 to investigated effect of varying levels of nitrogen and sulphur on growth and yield of coriander (Coriandrum sativum L.). Sixteen treatment combinations consisting of four levels each of nitrogen (20, 40, 60 and 80 kg N/ha) and sulphur (0, 10, 20 and 30 kg S/ha) replicated four times. Among the levels of nitrogen @ 80 kg ha-1 sowed its producing highest seed yield (1203 kg ha-1) and straw yield (1596 kg ha-1). The highest performance is attributed to significant improvement in growth and yields parameters viz., plant height, number of branches plant-1, number of umbels plant-1, number of umbellate umbel-1, number of seeds umbellate-1, Test weight (g) and seed weight plant-1 (g). Similarly application of nitrogen @ 80 kg ha-1 recorded highest quality parameters (protein content, volatile oil content and total oil yield) and uptake of nitrogen and sulphur . Among the levels of sulphur @ 30 kg ha-1 recorded significantly higher seed yield (1184 kg ha-1) and straw yield (1577 kg ha-1). Sulphur application @ 30 kg ha-1 significant improvement in growth and yield parameters viz., number of branches plant-1, number of umbels plant-1, test weight (g) and seed weight plant-1 (g). Application of sulphur @ 30 kg ha-1 also showed positive effect on protein, volatile oil content and total oil yield as well as uptake of nitrogen and sulphur.